Lajes lisas nervuradas bidirecionais de concreto armado sem armadura de cisalhamento com furos adjacentes ao pilar - AGUIAR, Amaury José Oliveira de (Universidade Federal do Pará, 2023)
With the need for a better understanding of the structural behavior of bidirectional ribbed flat slabs of reinforced concrete with opening adjacent to the column, aiming at the passage of installation ducts or ventilation, 15 square slabs measuring 2300 mm sides and 150 mm thickness with different opening configurations. The influence of the rectangularity of the columns was also an important topic analyzed, considering the concentration of tensions in the vertices of the loaded area. In order to do, 5 consecrated standards were used as a calculation parameter to estimate the final loads of the slabs and also to develop a new approach to estimate the loads of ruin. It is worth remembering that the analyzed slabs did not have shear reinforcement, that is, only the concrete contribution was considered to estimate the ultimate strength, although some standards associate this portion of resistance with the flexural reinforcement ratio, assigning an increase on ultimate strength. The results showed that the elongation of the opening and the column affected considerably the behavior of the slabs as well, the distribution of the stresses in the regions of the vertices of the openings. Based on data bases, it was possible to establish new parameters in the normative equations (Hi) which in turn approximated the results and decreased the dispersions of the same ones, besides a non-linear numerical analysis to have provided reliability standards in the models analyzed.